Perceptions toward cervical cancer screening participation among women in Gunungkidul District - Kusnia Wati Rahayu; Djaswadi Dasuki (Berita Kedokteran Masyarakat, 2021)
Purpose: This study aims to determine the association of perceptions with participation behavior in cervical cancer screening using VIA in Gunungkidul District. Methods: This research used a 1:1 unmatched case-control study design. The research sample consisted of 132 respondents (66 cases and 66 controls) selected by simple random sampling. Data collection was conducted through structured questionnaires administered during interviews from February to May 2019. Data analysis was done by chi-square test and multiple logistic regression. Results: Most respondents had an average age of 31-40 years, 47% had senior high school, 72% were housewives, and 78% had ≤ 2 children. Bivariate analysis results showed that perceptions (OR=19.74), knowledge (OR=3.09), and accessibility of health care (OR=7.87) were associated with participation in cervical cancer screening. Multivariable analysis results showed that the husband’s support was a significant confounder in the association between perceptions and cervical cancer screening participation. Conclusion: A good perception of cervical cancer and VIA screening will increase the chances of encouraging VIA screening participation behavior in women. Effective health education and community engagement by health workers, supported by local cadres, are essential to building accurate perceptions of cervical cancer and VIA screening. These efforts are expected to increase VIA screening coverage in the Gunungkidul District.